Theoretical study of the interaction of IRMOF-1 (MOF-5) with Valine, Alanine, and Norleucine amino acids - Moyosore, Abdullahi; Ahmad, Haslina; Abdel Malek, Emilia; Jumbri, Khairulazhar; Abdullah, Nor Ain Fathihah (Global Scientific Journal, 2022)
We have investigated by density functional theory the interaction of representative amino acids such as valine (Val), alanine (Ala) and norleucine (Nle) with a suitably functionalized organic linker of the IRMOF-1 (MOF-5) metal-organic framework. The binding energy value of -8.19 kcal/mol, -9.32 kcal/mol, and -5.64 kcal/mol were obtained via molecular docking for Val-MOF5, Ala-MOF-5, and Nle-MOF-5 complexes, respectively. Also, the intermolecular energy value and internal energy value for each of the complexes were found to very low, confirming their high stabilities and strong bonding between MOF-5 and the amino acids. This is very promising for possible pharmaceutical applications of MOF-5.